Investigation of inter- and intraspecies variation through genome sequencing of Aspergillus section Nigri. (December 2018) - Vesth, Tammi; Nybo, Jane; Theobald, Sebastian; Frisvad, Jens; Larsen, Thomas; Nielsen, Kristian; Hoof, Jakob; Brandl, Julian; Salamov, Asaf; Riley, Robert; Gladden, John; Phatale, Pallavi; et al.
Abstract Aspergillus sectionNigri comprises filamentous fungi relevant to biomedicine, bioenergy, health, and biotechnology. To learn more about what genetically sets these species apart, as well as about potential applications in biotechnology and biomedicine, we sequenced 23 genomes de novo, forming a full genome compendium for the section (26 species), as well as 6Aspergillus niger isolates. This allowed us to quantify both inter- and intraspecies genomic variation. We further predicted 17, 903 carbohydrate-active enzymes and 2, 717 secondary metabolite gene clusters, which we condensed into 455 distinct families corresponding to compound classes, 49% of which are only found in single species. We performed metabolomics and genetic engineering to correlate genotypes to phenotypes, as demonstrated for the metabolite aurasperone, and by heterologous transfer of citrate production toAspergillus nidulans . Experimental and computational analyses showed that both secondary metabolism and regulation are key factors that are significant in the delineation ofAspergillus species. De novo assembly of 23Aspergillus sectionNigri and 6Aspergillus niger genome sequences allows for inter- and intraspecies comparisons and prediction of secondary metabolite gene clusters.